Pengembangan Sistem Manajemen Pemesanan Barang Interior dan Eksterior Berbasis Web (Studi Kasus CV Omega Art Malang) - Yeremia Mus Mesak Ndaumanu; Adam Hendra Brata; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
CV Omega Art is a private company engaged in the sale, manufacture and installation of interior and exterior goods. In the company's development amid the rapid development of information technology, companies began to feel the need to develop access to company products and information that can be reached easily and more widely by customers. Through interviews with Business Owners, it was found that companies need an information system that can be used by customers to order products and display product information owned by the company. The company feels the need to display the official website as a form of company professionalism. Based on these needs, an interior and exterior goods ordering management system was developed that can help companies display the company's website, display the company's products, process product orders and attract customers to view and order products. The prototyping model is used to collect certain information about the information needs of users quickly. Users can use prototypes to screen and evaluate requirements. The application design is made with an object-oriented approach using the Model-View-Controller (MVC) design pattern. System implementation is done using the Laravel framework. Then, the developed system was tested using the Basis Path Testing method, validation testing, and Compatibility Testing. The results showed that the web-based interior and exterior goods ordering management system could accommodate the company's needs. The prototyping method is quite suitable to cover all requirements.